Evaluation of neonatally-induced mild diabetes in rats: Maternal and fetal repercussions - Iessi, Isabela L (BioMed Central, 2010)
Many experimental studies have been performed to evaluate mild diabetes effects. However, results are divergent regarding glycemia and insulin measurement, fetal macrossomia, and placental weights. The aim was to investigate repercussions of neonatally-induced mild diabetes on the maternal organism and presence of congenital defects in their offspring in other mild diabetes model. On the day of birth, female offspring were distributed into two groups: Group streptozotocin (STZ): received 100 mg STZ/kg body weight, and Control Group: received vehicle in a similar time period. Maternal weights and glycemias were determined at days 0, 7, 14 and 21 of pregnancy. At day 21 of pregnancy, the rats were anesthetized and a laparotomy was performed to weigh and analyze living fetuses and placentas. The fetuses were classified as small (SPA), appropriate (APA) and large (LPA) for pregnancy age. Fetuses were also analyzed for the presence of external anomalies and processed for skeletal anomaly and ossification sites analysis. Statistical significance was considered as p < 0.05. In STZ group, there was increased glycemia at 0 and 14 days of pregnancy, lower weights throughout pregnancy, higher placental weight and index, an increased proportion of fetuses classified as SPA and LPA, and their fetuses presented with an increased frequency of abnormal sternebra, and absent cervical nuclei, which were not enough to cause the emergence of skeletal anomalies. Thus, this study shows that mild diabetes altered fetal development, characterized by intrauterine growth restriction. Further, the reached glycemia does not lead to any major congenital defects in the fetuses of streptozotocin-induced mild diabetic rats.